An Analysis of Katie’s Low Self-Esteem and Feeling of Prestige in Sophie Kinsella’s My Not So Perfect Life - Anisa Rizki, Berliana; Manisa, Nur; Hardiyanti, Diana (Universitas Muhammadiyah Semarang, 2024)
This article analyzes the human needs in the novel. The novel tells the story of the main character who experiences feelings of low self-esteem and prestige in his life in the big city. This research aims to find out what and how the main character's needs are. This study uses a qualitative method with data obtained from sentences or dialog contained in the novel. The object of this research is the novel My Not So Perfect Life and is supported by secondary data such as theory books, and articles related to the topic of the problem. These problems can be formulated using Abraham Maslow's Theory of Human Needs, namely The Esteem Needs which helps the main character in meeting his needs. The results of this study can be concluded that in this novel the main character is in accordance with Abraham Maslow's theory of needs.